Making an IMPACT: A priority setting consultation exercise to improve outcomes in patients with locally advanced, recurrent and metastatic colorectal cancer. Issue 9 (September 2019) - Vallance, A.E.; Harji, D.; Fearnhead, N.S.; ,
Abstract: Aim: The IMPACT (Improving the Management of Patients with Advanced Colorectal Tumours) initiative was established by the Association of Coloproctology of Great Britain and Ireland in 2017 as a consortium of surgeons (colorectal, hepatobiliary, thoracic), oncologists, radiologists, pathologists, palliative care physicians, patients, carers and charity stakeholders who will work together to improve outcomes in patients with advanced and metastatic colorectal cancer. To establish this initiative, better information is required to establish how further intervention is focused. This paper details the approaches used, and outcomes generated, from a priority setting exercise to inform the design of the IMPACT initiative. Methods: A mixed method approach was employed to set the priorities of patients, clinicians and other key stakeholders in the delivery of optimal care. This consisted of two patient centered consultation events and a questionnaire. Results: A total of 128 participants took part in the consultation exercise; 15 patients, 5 carers/family members, 5 charity representatives and 113 healthcare professionals. Nine key themes for focus were identified, these were: current service provision, specialist services, communication, education, access to care, definitions and standardisation, research and audit, outcome measures, and funding of specialist care. Conclusion: These future priorities will be developed with collaborative engagement in a systematic manner to produce an overall cohesive programme which will deliver a sustainable and efficient clinical and academic service to improving the management of patients with advanced colorectal tumours.